Top Answer

144, you add the plus numbers, then multiply it by the first.

🌎

0🤨

0😮

0😂

0Loading...

96

26

144

144

If I am correct, 9 plus 7 equals 112.

2+3 = 5 * 2 = 10. 7+2 = 9 * 7 = 63.6+5 = 11 * 6 = 66.x+y = z * x = n.9+7 = 16 * 9 = 144

144, you add the plus numbers, then multiply it by the first.

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

144 add the two numbers and multiply by the first 2(2 + 3) = 10 7(7 + 2) = 63 etc.

144 9+7 = 16 and 9*16 = 144

273 13+8 = 21 and 13*21 = 273

144 is the answer.2+3=10 which means 2+3=55*2=107+2=63 7+2=99*7=63now 9+7=? 9+7=1616*9=144

2 squared plus 2 x 3 = 10, 7 squared plus 7 x 2 = 63, 6 squared plus 6 x 5 = 66,8 squared plus 8 x 4 = 96 so 9 squared plus 9 x 7 = 81 + 63 = 144.

35

66 times 6 equals 396.

144 (square the first value and add the product of the two values). In the statement 7 + 6 should = 91, not 63, which would be 7 + 2.

144 9+7 = 16 and 9*16 = 144

66 plus 66 equals 132

9 plus 7 equals 144. Generally, x plus y = x(x+y).

This or a similar question has already been answered. 2_plus_3_equals_10_7_plus_2_equals_63_6_plus_5_equals_66_8_plus_4_equals_96_then_9_plus_7_equals_what144.

18 + 10 + 28 + 10 = 66

then 4 plus 3 equals 28 and 3 plus 3 equals 18 and 7 plus 5 equals 84 .... its easy you just have to multiply the answer with the first number.. for example : 2 plus 3 equals 5 but when you multiply the answer with the first number (2) it becomes equals 10, and so on the others..